Активи підприємства і шляхи підвищення ефективності їх використання (на прикладі ТОВ «ЖДТ-Сервіс», м. Кропивницький) - Добровольський, Вадим Олександрович; Dobrovolskyi, Vadym (ЦНТУ, 2024)
Розглянуто теоретико-методичні основи до визначення активів підприємства та резервів підвищення їх ефективності, визначення сутності, змісту та складових елементів активів підприємства, розгляд методичних засад управління активами підприємств, політика та стратегія управління активами підприємства. Проаналізовано управління активами ТОВ «ЖДТ-Сервіс», розглянуто організаційно-економічну характеристику ТОВ «ЖДТ-Сервіс», проведено фінансово-економічний аналіз діяльності ТОВ «ЖДТ-Сервіс», проведено аналіз активів ТОВ «ЖДТ-Сервіс». Розглянуто напрямки удосконалення управління активами підприємства, окреслено напрямки оптимізації управління активами підприємства, та напрямки удосконалення діагностики політики управління активами підприємства. The theoretical and methodological foundations for determining the assets of the enterprise and reserves for increasing their efficiency, determining the essence, content and components of the assets of the enterprise, considering the methodological principles of managing the assets of enterprises, the policy and strategy of managing the assets of the enterprise are considered. The asset management of LLC "ZHDT-Service" is analyzed, the organizational and economic characteristics of LLC "ZHDT-Service" are considered, a financial and economic analysis of the activities of LLC "ZHDT-Service" is conducted, and the assets of LLC "ZHDT-Service" are analyzed. The directions for improving the management of the assets of the enterprise are considered, the directions for optimizing the management of the assets of the enterprise are outlined, and the directions for improving the diagnostics of the asset management policy of the enterprise are outlined.
Assets of the enterprise and ways to improve the efficiency of their use
Keywords: активи підприємства; управління активами підприємства; політика управління активами підприємства; стратегія управління активами підприємства; enterprise assets; enterprise asset management; enterprise asset management policy; enterprise asset management strategy